Ethanolic Extract of the Red Algae Meristiella echinocarpa (Areschoug) Confers Neuroprotection in Mice - dos Santos, Mayula Mirely; Assreuy, Ana Maria Sampaio; Oliveira, Luis Gustavo Farias; Alencar, Daniel Barroso de; Sampaio, Silvana Saker; Sampaio, Alexandre Holanda; Chaves, Edna Maria Camelo; Sampaio, Alexandre; Aragão, Gislei Frota (Journal of Health & Biological Sciences, 2021)
Objectives: This study aimed to investigate the neuroprotective effects of the ethanolic extract obtained from red algae marine Meristiella echinocarpa (Areschougiaceae) – EEMe. Methods: EEMe was used in doses ranging from 10 to 40 mg/kg, administered intraperitoneally in mice. Behavioral tests were performed to assess locomotor activity (open field), anxiety (elevated plus maze), depression (tail suspension), and motor coordination (rota-rod). The anticonvulsant effect of the algae extract was evaluated in two models of seizures induced by strychnine and pentylenetetrazol. The level of oxidative stress was also evaluated in the following brain areas: the prefrontal cortex, hippocampus, and striatum. Statistical analysis was performed applying ANOVA followed by the Bonferroni test. Results: EEMe reduced significantly the number of crossing (36%) and rearing (54%) in the open field test and increased 1.3x the immobility time in the tail suspension test. In brain areas EEMe also reduced significantly malondialdehyde levels (striatum: 45%, hippocampus: 38%, prefrontal cortex: 37%) and nitrite levels (striatum: 72%, hippocampus: 79%, prefrontal cortex: 63%), and increased the reduced-glutathione levels (striatum: 72%, hippocampus: 73%, prefrontal cortex: 42%). In addition, the extract significantly prolonged the latency of seizures induced by strychnine (38%) or pentylenetetrazol (57%), and the latency of death induced by pentylenetetrazol (6.1x). Conclusion: EEMe exhibits antioxidant and anticonvulsant effects, probably involving GABAergic and glycinergic pathways. extract exhibits antioxidant and anticonvulsant effects, involving GABAergic and glycinergic pathways.